2012
DOI: 10.1016/j.neuropsychologia.2012.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Neural evidence of allophonic perception in children at risk for dyslexia

Abstract: Learning to read is a complex process that develops normally in the majority of children and requires the mapping of graphemes to their corresponding phonemes. Problems with the mapping process nevertheless occur in about 5% of the population and are typically attributed to poor phonological representations, which are--in turn--attributed to underlying speech processing difficulties. We examined auditory discrimination of speech sounds in 6-year-old beginning readers with a familial risk of dyslexia (n=31) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 66 publications
5
40
0
2
Order By: Relevance
“…This theory suggests that speech perception is not degraded in DD on an acoustic level, but instead, not adequately attuned to the phonetic contrasts present in the native language. This hypothesis has further been supported using behavioral and neuroimaging measures in children at risk for DD (Noordenbos, Segers, Serniclaes, Mitterer, & Verhoeven, 2012a, 2012b. With regard to speech production, it has been shown that both articulatory skills (Catts, 1986(Catts, , 1989 and oral motor skills are impaired in people with DD (Malek, Amiri, Hekmati, Pirzadeh, & Gholizadeh, 2013;Smith, Roberts, Lambrecht-Smith, Locke, & Bennett, 2006).…”
Section: A Phonological Processing Deficit In Ddmentioning
confidence: 84%
“…This theory suggests that speech perception is not degraded in DD on an acoustic level, but instead, not adequately attuned to the phonetic contrasts present in the native language. This hypothesis has further been supported using behavioral and neuroimaging measures in children at risk for DD (Noordenbos, Segers, Serniclaes, Mitterer, & Verhoeven, 2012a, 2012b. With regard to speech production, it has been shown that both articulatory skills (Catts, 1986(Catts, , 1989 and oral motor skills are impaired in people with DD (Malek, Amiri, Hekmati, Pirzadeh, & Gholizadeh, 2013;Smith, Roberts, Lambrecht-Smith, Locke, & Bennett, 2006).…”
Section: A Phonological Processing Deficit In Ddmentioning
confidence: 84%
“…(25) Netherland To verify the speech sound discrimination, through the MMN, in children at risk for dyslexia.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the place of publication, most articles, totaling 6 (21,28,35,36,38,39) , were developed in Finland. Three articles were written in Brazil (4,12,19) , 3 in the Netherlands (20,23,25) , 3 in the United States (31,32,34) and 3 in France (26,29,30) . Studies have also been found in China (24,27) , Germany (33) , Canada (22) and Israel (37) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations